Black Beauty - Sewell, Anna; Levine, Gail Carson (New York F. Watts, 2007)
A horse in nineteenth-century England recounts his experiences with both good and bad masters
Includes a study guide
Originally published : 1877
Hurg
5 8
Keywords: Great Britain -- History -- 19th century -- Fiction; Horses -- Fiction